Efficacy of autologous mesenchymal stromal cell treatment for chronic degenerative musculoskeletal conditions in dogs: A retrospective study - Armitage, Andrew J.; Miller, Joanna M.; Sparks, Tim H.; Georgiou, Alex E.; Reid, Jacqueline (Frontiers in Veterinary Science, 2023)
The objective of this study was to retrospectively analyse clinical data from a referral regenerative medicine practice, to investigate the efficacy of autologous mesenchymal stromal cells (MSC) in 245 dogs deemed unresponsive to conventional treatment by their referring vet. Diagnostic imaging (radiology and musculoskeletal ultrasound (MSK-US)) identified musculoskeletal pathology holistically. MSCs, produced according to current guidelines, were initially administered with PRP by targeted injection to joints and/or tendons, with a second MSC monotherapy administered 12 weeks later to dogs with severe pathology and/or previous elbow arthroscopic interventions. Dogs with lumbosacral disease received epidural MSCs with additional intravenous MSCs administered to dogs with spondylosis of the cervical, thoracic and lumbar spine. All dogs received laser therapy at 10 J/cm2 at the time of treatment and for 5 sessions thereafter. Objective outcome measures (stance analysis, range of joint motion, pressure algometry) and validated subjective outcome measures (owner reported VetMetrica HRQL™ and veterinary pain and quality of life impact scores) were used to investigate short and long-term (6-104 weeks) efficacy. Outcome data were collected at predetermined time windows (0-6, 7-12, 13-18, 19-24, 25-48, 49-78, 79-104) weeks after initial treatment. There were statistically significant improvements in post compared with pre-treatment measures at all time windows in stance analysis, shoulder and hip range of motion, lumbosacral pressure algometry, and to 49-78 weeks in carpus and elbow range of motion. Improvements in 4 domains of quality of life as measured by VetMetricaTM were statistically significant, as were scores in vet-assessed pain and quality of life impact. In dogs receiving one initial treatment the mean time before a second treatment was required to maintain improvements in objective measures was 451 days. Diagnostic imaging confirmed the regenerative effects of MSCs in tendinopathies by demonstrating resolution of abnormal mineralisation and restoration of normal fibre patterns. This represents the first study using ‘real-world’ data to show that cell-based therapies, injected into multiple areas of musculoskeletal pathology in a targeted holistic approach, resulted in rapid and profound positive effects on the patient’s pain state and quality of life which was maintained with repeat treatment for up to 2 years.